PERUBAHAN DAN KONTINUITAS SENI BARONGSAI DI SURAKARTA PASCA REFORMASI - Wahyudiarto, Dwi (Acintya, 2009)
This article is based On individual research focussed on barongsai and its journey in Surakarta after the reformation era. Barongsai art performance in New Orde era is paid less attention as a creative pmduct. It has developed after post reformation era. This kind of Chinese ethnic performance has changed artistically and technically after the reformation era. Barongsai, in the former~ is usedfor ritual usage and it has been changing nowadays especially for social funcion. This article examines baron gsai of Chinese ethnic through special approach and interpretative description based on its data sources empirically. Barongsai art performance as an material object would be exposed as much as possible while it is accompanied by everything which supports its existence nowdays. Several things indicate that baron gsai appearence had been supported by ritual needs, social needs, aesthetic needs, and existence needs. Barongsai and its development during the post reformation era give much impact to its existence connected to afair regulation and the changes of societiy which gradually welcoming upon this kind of art performance. Even it is often related to the frequently shows increase among Chinese ethnic who perform the barongsai and it shows us, in other way, that the creative world must be appeared in the field ofperforining arts. Keywords: barongsai, continuities, change, reformation